Little visits for families - Jahsmann, Allan Hart.; Simon, Martin P.; Lund, Hal (St. Louis, MO : Concordia, 1995)
A collection of more than 150 devotions on such topics as daily activities, the Ten Commandments, and holidays. Includes interactive discussion questions, Bible verses, and prayers.
Originally published: More little visits with God. St. Louis, MO : Concordia, 1961.
Includes index.
Keywords: Families -- Prayers and devotions; Prayer books and devotions; Christian life